Harassment at work: psychometric evidence of the LIPT-60 in a Peruvian simple - Rosales Shishco, Silvia Elizabeth (2018)
The objective of the study is to determine the psychometric properties of the questionnaire of strategies of harassment at work (LIPT - 60), in a Peruvian sample of 320 teachers from public primary and secondary schools in Chimbote and Nuevo Chimbote, elected by strata. The results ratified the original model of the instrument, composed of 60 items, distributed by 06 factors. The factorial structure was confirmed, through the method of unweighted least squares, where the goodness-of-fit index (GFI = .959), the adjusted goodness-of-fit index (AGFI = .989), and the average root of squared residuals are reported ( RMR = .041); likewise, the comparative adjustment is obtained (NFI = .999). An item-test correlation was found above, 80 indicating an optimum level in the list of reactants. The reliability for internal consistency through McDonald's Omega coefficient with an index between .959 to .986, of high appreciation. Keywords: Labor harassment, validity, reliability.